2021
DOI: 10.2172/1811299
|View full text |Cite
|
Sign up to set email alerts
|

Energy Storage in South Asia: Understanding the Role of Grid-Connected Energy Storage in South Asia’s Power Sector Transformation

Abstract: Department of Energy (DOE) reports produced after 1991 and a growing number of pre-1991 documents are available free via www.OSTI.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Emerging low-cost energy storage from lithium-ion battery technologies has the potential to offset the need for new investments in fossil-fueled capacity. In India, for example, NREL's recent study showed that 4-hour duration storage devices could provide about 70 GW of reliable capacity at 100% capacity credit in 2030 (Chernyakhovskiy et al 2021). The same study also demonstrated the potential risk of excluding the capacity contribution of energy storage in the planning process.…”
Section: Including Capacity From Storage Effects the System Needsmentioning
confidence: 95%
See 4 more Smart Citations
“…Emerging low-cost energy storage from lithium-ion battery technologies has the potential to offset the need for new investments in fossil-fueled capacity. In India, for example, NREL's recent study showed that 4-hour duration storage devices could provide about 70 GW of reliable capacity at 100% capacity credit in 2030 (Chernyakhovskiy et al 2021). The same study also demonstrated the potential risk of excluding the capacity contribution of energy storage in the planning process.…”
Section: Including Capacity From Storage Effects the System Needsmentioning
confidence: 95%
“…In addition to system-wide evolution, technologies such as energy storage in the form of batteries will necessitate innovation to planning and operating processes. Several studies have identified India as a potentially large market for energy storage (Chernyakhovskiy et al 2021;Abhyankar, Deorah, and Phadke 2021), and some local systems have started to emerge (Tata Power 2021). However, several questions about the optimal use of these systems, the value that they provide, and their interdependence on renewable energy, remain.…”
Section: Near-term Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations